2012
DOI: 10.5539/ijb.v4n3p140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urea as Nitrogen Source and Pix as Growth Regulator on Cotton (Gossypium hirsutum L)

Abstract: In order to study the effects of the application of various amounts of nitrogen fertilizers and Pix 35% growth regulator on the morphological features of the Sahel cultivar of cotton (Gossypium hirsutum L.), and on the unginned cotton yield of this cultivar, an experiment was carried out in the factorial design in the randomized complete block format with three replications at the Bayekola Agronomical Research Station in 2009. The factors studied included the amounts of nitrogen fertilizers and of the cotton g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Treatments i.e., T2, T3, T4 also showed significant improvement in these parameters compared to the control but to a lesser extent compared to T5. Similarly, the findings of our investigation are in line with the findings of previous studies Choudhary et al, 2018;Zaidi et al, 2020) which reported that the application of NPK fertilizers enhanced the growth and yield of cotton. These studies also emphasized the positive role of NPK fertilizers in improving soil fertility and crop productivity under alkaline soil conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Treatments i.e., T2, T3, T4 also showed significant improvement in these parameters compared to the control but to a lesser extent compared to T5. Similarly, the findings of our investigation are in line with the findings of previous studies Choudhary et al, 2018;Zaidi et al, 2020) which reported that the application of NPK fertilizers enhanced the growth and yield of cotton. These studies also emphasized the positive role of NPK fertilizers in improving soil fertility and crop productivity under alkaline soil conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Foliar spray of nutrients and plant growth regulators is the fastest way to boost crop growth because the nutrients are available to plants at the initial and critical stages [20]. Foliar application of plant growth regulators could increase leaf area index, dry matter accumulation, delay root senescence and increase crop yield [25,26].…”
Section: Productivity and Seed Yieldmentioning
confidence: 99%
“…The experimental design incorporates various treatments, including 19:19:19 NPK, Brassinosteroid, and Salicylic Acid, both individually and in consortia. The study aims to elucidate the impact of these treatments on parameters such as Crop Growth Rate (CGR), Leaf Area Index (LAI), Relative Water Content (RWC), and SPAD Chlorophyll Meter Readings (SCMR) post-flowering (Esmaeil et al, 2012). The outcomes of this research are expected not only to contribute valuable insights into optimizing finger millet management practices under water stress but also to provide a foundation for future investigations into the application of foliar strategies across diverse crops and under different stress conditions.…”
Section: Introductionmentioning
confidence: 99%